Ou sont mes ailes ? / Where Are My Wings? - Toure, Soutcho Lydie (Book collections on Project MUSE., 2019)
"Don't sit on your stool, watching life go by," insists Soutcho Lydie Toure. In this collection of reflections written over a decade, she explores insecurities and vulnerabilities, with which many a reader will relate. She shares about loneliness and feeling different and goes on to ponder everyday life in "Politicking" and "VDN"--A memorable highway in Dakar which pedestrians must cross "under the mocking smile of the sun." Toure draws on experiences and insights from her life betwixt and between West Africa and North America. In her verses, spiced with nature, color, joy, humor and fantasy, questions and answers compete equally for the reader's attention. A veritable source of confidence in the force of life and love. Confidence that makes one grow wings